2003
DOI: 10.1002/jemt.10268
|View full text |Cite
|
Sign up to set email alerts
|

The circadian system of crayfish: A developmental approach

Abstract: Adult crayfish exhibit a variety of overt circadian rhythms. However, the physiological mechanisms underlying the overt rhythms are controversial. Research has centered on two overt rhythms: the motor activity and the retinal sensitivity rhythms of the genus Procambarus. The present work reviews various studies undertaken to localize pacemakers and mechanisms of entrainment responsible for these two rhythms in adult organisms of this crustacean decapod. It also describes an ontogenetic approach to the problem … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
33
0
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 85 publications
(81 reference statements)
5
33
0
1
Order By: Relevance
“…In the lobster H. americanus, light-entrainable circadian changes in 5-HT concentrations have been observed in both the central brain and the eyestalk (249). Changes in the circadian rhythm of 5-HT (and likely its ratelimiting enzyme tryptophan-hydroxylase; 250) during crayfish development according to a 9-12 hr rhythm have been interpreted as (i) being superimposed upon the basic circadian rhythm (248) or (ii) representing an example for an initially ultradian-like rhythmicity of, e.g., the ERG and retinal shielding pigment movements (15min to 4hrs), that about 30 days later is being replaced by circadian rhythmicity as has been shown for first instar crayfish P. clarkii (22).…”
Section: Serotoninmentioning
confidence: 99%
See 2 more Smart Citations
“…In the lobster H. americanus, light-entrainable circadian changes in 5-HT concentrations have been observed in both the central brain and the eyestalk (249). Changes in the circadian rhythm of 5-HT (and likely its ratelimiting enzyme tryptophan-hydroxylase; 250) during crayfish development according to a 9-12 hr rhythm have been interpreted as (i) being superimposed upon the basic circadian rhythm (248) or (ii) representing an example for an initially ultradian-like rhythmicity of, e.g., the ERG and retinal shielding pigment movements (15min to 4hrs), that about 30 days later is being replaced by circadian rhythmicity as has been shown for first instar crayfish P. clarkii (22).…”
Section: Serotoninmentioning
confidence: 99%
“…Several crustacean clocks have previously been reviewed with regard to both circadian (10,(19)(20)(21)(22) and circatidal (3,4,6,8,19) rhythms, just to mention only some more recent or extensive works. Whilst ultradian rhythms have been detected in many systems (12), their functional significance has yet to be determined.…”
Section: Chronobiological Systems In Crustaceamentioning
confidence: 99%
See 1 more Smart Citation
“…In other crustaceans such as the fiddler crab Uca pugilator and the crayfish Procambarus clarkii, fluctuating serotonin levels have mostly been described for eyestalks (Fingerman and Fingerman, 1977;Fingerman et al, 1978;EscamillaChimal et al, 2001;Fanjul-Moles and Prieto-Sagredo, 2003). Castanon-Cervantes et al (1999) are the only authors to our knowledge who have assessed serotonin levels over 24·h in the brain of another crustacean.…”
Section: Discussionmentioning
confidence: 99%
“…This could potentially alter the behaviour and movement patterns in crayfish and act as a behavioural barrier to dispersal. It has been shown that crayfish behaviour is influenced by changes in light intensity (Fanjul-Moles and Prieto-Sagredo, 2003;Fanjul-Moles et al, 2004), and even species that live in dark caves exhibit circadian entrainment (Jegla and Poulson, 1968). Studies on potential behavioural obstacles as a result of dark culverts have, so far, unsurprisingly, focused on fish.…”
Section: Introductionmentioning
confidence: 99%